Ratio of Native Grass and Concentrate in the Ration to the Quality of Milk Production of Holstein Cow - Suherman, Dadang (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
The research attempted to find out ratio of native grass and concentrate in the ration to the quality of milk production of Holstein cow. Latin Square Design was used with five treatments of ratio of native grass and concentrate ( 70 : 30%, 60 : 40%, 50 : 50%, 40 : 60%, 30 : 70%), applied using five Holstein cows at the third lactation periode and the third mounth of lactation. The variable measured were in the quality milk production consist of actual milk yield, the milk fat content, crude protein, solid non fat, efficiency ofÂ energy bruto and energy netto, and income over feed cost. The best ratio of native grass and concentrate in the ration for the efficiency of energy bruto, energy netto and income was 50 : 50%. The milk fat content and actual milk yield have relationship form with the milk energy value. The best ratio of native grass and concentrate in the ration to increasing the milk fat content, crude protein and crude of solid non fat was 70 : 30%. (Animal Production 7(1): 14-20 (2005)Â Key Words : Native grass, concentrate, energy bruto, energy netto